Inuit woman (Nivisanaaq) using sewing machine on board whaling schooner (Hudson Bay, Canada area) - Comer, George (Creator); American Museum of Natural History (Creator) (Ownership Statement: Mystic Seaport, 1907)
An Aivilik Inuit woman identified as "Shoofly" (Nivisanaaq) is using a sewing machine in the deckhouse of a whaling schooner, probably the A.T. Gifford, Hudson Bay, Canada, area. Lifestyle Livelihood Infrastructure Title supplied by cataloger. The schooner A.T. Gifford was built in 1883 at Essex, Massachusetts. George Comer was her master during one of his Arctic voyages in which he mapped areas in the Hudson Bay area. Taken by Captain George Comer (1858-1937), a sealer and whaling captain from East Haddam. He went to sea while still in his teens and was later master of vessels from both New London and New Bedford. Comer participated in voyages involved in polar expeditions and was noted for his studies of Arctic peoples and their environment. Slide prepared by the American Museum of Natural History, New York, from an original photograph by Captain George Comer. Slide was used by Comer to illustrate lectures about his Arctic and seafaring experiences. Comer and the American whalers were closely associated with the Aivilik or Aivillingmiut group of Iglulik Inuit for many years.